2015
DOI: 10.5539/elt.v8n9p40
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Attitudes towards Blended Learning for English Courses: A Case Study of Students at University of Bisha

Abstract: This paper presents a case study of students' perceptions and attitudes towards Blended Learning course in English at University of Bisha. The statement of problem that blended learning of English course annoys students at University of Bisha. Most of the students do not understand well the objectives of e learning through blended learning courses or mostly deal with the blackboard system "Learning Management System" (LMC). This paper identifies the perceptions and attitudes that blended learning provides to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 11 publications
2
16
0
Order By: Relevance
“…Several studies investigating the challenges of BL have identified several problems faced by institutions, such as a lack of Internet connectivity, technical issues, workload, and confusing instructions in Blackboard (Al Zumor et al, 2013;Banditvilai, 2016;Guangying, 2014;Hamdan et al, 2017;Ja'ashan, 2015;Poon, 2013;Thang et al, 2012) as well as difficulties encountered by students, (Alshathri, 2016;Hamad, 2017;Ja'ashan, 2015;Thang et al, 2012;Vaughan, 2007) and instructors (Alaidarous & Madini, 2016;Alebaikan & Troudi, 2010;Badawi, 2009;Yang, 2012). Ja'ashan (2015) examined 130 undergraduate students' perceptions toward challenges in BL in an English module.…”
Section: Potential Challenges Of Using Bl To Support English Languagementioning
confidence: 99%
“…Several studies investigating the challenges of BL have identified several problems faced by institutions, such as a lack of Internet connectivity, technical issues, workload, and confusing instructions in Blackboard (Al Zumor et al, 2013;Banditvilai, 2016;Guangying, 2014;Hamdan et al, 2017;Ja'ashan, 2015;Poon, 2013;Thang et al, 2012) as well as difficulties encountered by students, (Alshathri, 2016;Hamad, 2017;Ja'ashan, 2015;Thang et al, 2012;Vaughan, 2007) and instructors (Alaidarous & Madini, 2016;Alebaikan & Troudi, 2010;Badawi, 2009;Yang, 2012). Ja'ashan (2015) examined 130 undergraduate students' perceptions toward challenges in BL in an English module.…”
Section: Potential Challenges Of Using Bl To Support English Languagementioning
confidence: 99%
“…Researchers focused on attitudes and perceptions (Al Zumor et al, 2013;Ja'ashan, 2015;Alaidarous & Madini, 2016) and as improving listening and speaking skills (Hussein, 2016).…”
Section: Review Of Literaturementioning
confidence: 99%
“…While in the "don't really like" category, there are only three women included in the category and there are ten statements that are agreed, one of which is students can read anywhere and at any time to re-understand mathematical material if the educator provides online teaching material. As revealed by several studies that technology in online media can make it easier for students to understand learning material (Adams, Sumintono, Mohamed, & Noor, 2018;Cheok, Wong, Ayub, & Mahmud, 2017;Hassan Ja'ashan, 2015). On the other hand, figure 2 and table 2 show that only subjects from the provinces B, C, and D liked BL in teaching mathematics, the percentage is 3.7%, 7.4%, and 3.7%, respectively.…”
Section: Resultsmentioning
confidence: 99%